Espaço, memória e identidade em Dois irmãos, de Milton Hatoum - Silva, Alex Bruno da (2018)
In this research we propose an analysis of the novel Dois irmãos, by Milton Hatoum, in order to verify the interweaving between memory, space and identity. In this novel, Hatoum manages to interweave the space of the house and the city of Manaus with the narrator's need to fill the voids of his story, which leads us to the hypothesis that the representation of space, in the novel Dois irmãos, plays a preponderant role in the construction of the narrator's subjective memory. This research hypothesis is based on the following questions: a) What is new in the theme of memory in Dois irmãos, which leads us to reflect on the experiences of the contemporary subject? and b) how does the representation of space affect the subjectivity of the characters and allows us to think about identity in contemporary society? To answer these questions and reflect on the hypothesis raised, we chose to structure this work into two chapters, in which theory and criticism are associated with the analysis of the fictional text in a dialogical way. The treatment given to memory, space and identity is imbricated in the context of the novel Dois irmãos so that when talking about the narrator's memory and the constructions of characters identities, the spatial aspect is indispensable to understand this relation. Thus, in the first chapter titled "Threads of Stories: Weaving Memories in Dois irmãos by Milton Hatoum," we will problematize how the theme of memory deals with the relation between memory and forgetfulness, reality and imagination, individual and collective aspects, to think about the rescue of memory in a contemporary society. To understand memory, from a traumatic event, we will base our reflections and discussions on the propositions of Walter Benjamin (1985), Jeanne Marie Gagnebin (2009), Márcio Seligmann-Silva (2002/2003/2008), Michael Pollak (1989), Primo Levi (2004) and Maurice Halbwachs (2006), to establish a dialogue with other critics and observe the meanings of memory in Hatoum's novel. In the second chapter, entitled "Spaces in Ruins: Traffic Pictures in Dois irmãos, by Milton Hatoum," we will look at some aspects of space construction in Hatoum's narratives to think about the relationship between space and characters. The theoretical-critical contribution used to analyze this relationship between space and subject refers us to the studies of Osman Lins (1976), Michel de Certeau (2014), Oziris Borges Filho (2007), Luis Alberto Brandão (2013/2015), Doreen Massey (2015), among others. In this chapter we will also examine, from a Cultural Studies perspective, the meanings of traffic, exile and wandering, to raise some questions that specifically concern the condition of the immigrant subject in constant spatial displacement. The representation of the city and the spaces of intimacy will also be observed as places of social and subjective practices of the subject to reveal with these spaces, they reveal lived experiences that, in the narrative, are filtered by the narrator's gaze and (re)constructed by means of your memory.